Bridging-nitrogen defects modified graphitic carbon nitride nanosheet for boosted photocatalytic hydrogen production. (3rd August 2021) - Luo, Lei; Wang, Keran; Gong, Zhuyu; Zhu, Haixing; Ma, Jiani; Xiong, Lunqiao; Tang, Junwang
Abstract: Reinforcing the visible photon absorption and charge separation are the key issues to maximize the photocatalytic performance of graphitic carbon nitride. Herein, holey bridging-nitrogen-defected graphitic carbon nitride nanosheets were prepared through solid-state copolymerization and subsequently thermal annealing with melamine and hexamethylenetetramine as the precursors. Numerous pores and bridging nitrogen defects that embedded into the thin-layer framework were evidenced through comprehensive characterization. The synthesized textural and electronic structure enables the significant improvement of photocatalytic hydrogen production, with the optimized sample of D-CNNS(0.3) representing a hydrogen evolution rate of 2497.1 μmol∙g −1 ∙h −1 under visible light irradiation (λ > 420 nm). This is about 10.4 and 41.1 folds improvement compared with pristine nanosheets and bulk carbon nitride, respectively. Both experimental and theoretical results demonstrate the bridging nitrogen defects are beneficial to enhance photoabsorption, promote charge separation and transfer. Together with the enlarged surface area, the optimized nanosheet sample shows a dramatically improved quantum yield in visible region. Graphical abstract: Image 1 Highlights: Bridging-nitrogen defects modified g-C3 N4 nanosheets were facilely prepared. Textural and electronic structures were simultaneously regulated. Optimized H2 production reached 2495.1 μmol g −1  h −1 (λ > 420 nm). Apparent quantum yield was 3.24% at 420 ± 10 nm. Photoabsorption and charge separation could be induced by bridging-nitrogen defects.